Achievement motivation in the leadership role of extension agents - Karami, Roya; Ismail, Maimunah (Cambridge Scholars Publishing, 2012)
This book is relevant to the practice and theory of agricultural extension. In the current context of significant changes in thinking, policy, and expectations, these changes require extension agents to respond to challenges in developing leadership skills to support and encourage changes at farm and household levels. The book has identified the background, personal, and environmental factors influencing achievement motivation in leadership role of extension agents. The background factors are primary dimensions of diversity and are less amenable to change, exert significant impacts, and shape our basic self-image, sense of identity, and early learning experiences. Researchers often ignore the interdependence of the background factors with other (secondary) dimensions of diversity, in which the latter are changeable personal characteristics that are acquired, and may be modified or abandoned throughout life. Although the secondary dimensions of diversity are more controllable, they will be affected by other people's decisions, which in this book we see as environmental factors. The reliability and applicability of the above-mentioned theoretical discussion have been tested in an original study involving extension agents in Iran.